1993
DOI: 10.1016/0014-5793(93)80206-a
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic peptide of the N‐terminus of ADP‐ribosylation factor (ARF) inhibits regulated exocytosis in adrenal chromaffin cells

Abstract: We have investigated the role of ADP-~bosylation factor (ARF) in regulated exocytosis in di~tonin-~~eabil~ed adrenal chroma& cells by the use of a synthetic peptide, hARFl(Z-17), based on the N-terminus of the protein hARF1(2-17) inhibited &+-dependent but not basal exocytosis, whereas equimoiar leveis of other synthetic peptides were ineffective. The inhibitory effect of hARFl(Z-17) was dose-dependent and half-maximal at 12 ,uM. GTPyS-induced secretion in the presence of non-stimulatory CA*+ concentrations wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…To date, studies that address ARF function have been few. In chromaffin cells, SG-associated ARF has been implicated in exocytosis on the basis that ARF peptide inhibits calcium-dependent secretion (Morgan and Burgoyne, 1993;Galas et al, 1997) and GTPyS-stimulated PLD activity and exocytosis (Fensome et al, 1996). An ARF-like protein, ARL 184, was also shown to potentiate acetylcholine release in stably transfected PC12 cells (Icard-Liepkalns et al, 1997).…”
Section: Arfmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, studies that address ARF function have been few. In chromaffin cells, SG-associated ARF has been implicated in exocytosis on the basis that ARF peptide inhibits calcium-dependent secretion (Morgan and Burgoyne, 1993;Galas et al, 1997) and GTPyS-stimulated PLD activity and exocytosis (Fensome et al, 1996). An ARF-like protein, ARL 184, was also shown to potentiate acetylcholine release in stably transfected PC12 cells (Icard-Liepkalns et al, 1997).…”
Section: Arfmentioning
confidence: 99%
“…Important studies in this regard were reported by Vitale et al (1993) (Oberhauser et al, 1992) and pancreatRapl ic acini (Piiper et al, 1995), and in chromaffin cells (Senyshyn et al, 1992). Also, in permeabilized chromaffin cells, the synthetic peptide hARF (2-17) (Morgan and Burgoyne, 1993) and myristoylated and nonmyristoylated ARF6 (2-13), synthetic peptides corresponding to residues 2-13 of ARF6, produced a dose-dependent inhibition of calcium-dependent catecholamine release (Galas et al, 1997). In some studies, due to reported non-specific effects of peptides, the validity of the data obtained has been debated.…”
Section: Introductionmentioning
confidence: 98%
“…MyrARF6 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) produced a dose-dependent inhibition in Ca 2ϩ -dependent catecholamine secretion with a mean inhibitory dose, ID 50 , of approximately 40 M (Fig. 3).…”
Section: Effect Of the N Terminus Arf6 Synthetic Peptides On Ca 2ϩ -Ementioning
confidence: 99%
“…For example, rab3 isoforms which are specifically localized on the membrane of secretory vesicles (7,8), have been proposed to serve as a regulator of exocytosis in chromaffin cells (9) and in anterior pituitary cells (10). Other investigations have postulated the participation of ARF in exocytosis (11,12).…”
mentioning
confidence: 99%
“…Specific members of this superfamily have been considered as mediators of these GTP effects on exocytosis, including heterotrimeric G proteins (5-9) and low molecular weight ras-like proteins such as Rab (10)(11)(12)(13)(14)(15) and ARF (16). The current "fusion machine" hypothesis (17)(18)(19) envisions a core complex formed between plasma membrane syntaxin and SNAP-25 and the synaptic vesicle protein synaptobrevin/VAMP (20), with vesicular synaptotagmin putatively identified as a low-affinity calcium sensor that interacts with regulatory syntaxin 1 (21,22).…”
Section: Gtp and Its Nonhydrolyzable Analogue Guanosine 5'-[y-mentioning
confidence: 99%